The presence of collagen types II and X in medial coronoid processes of 21 dogs - Crouch, D. T.; Cook, J. L.; Lewis, D. D.; Kreeger, J. M.; Tomlinson, J. L. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The purpose of this study was to determine collagen type II and X immunohistochemical staining characteristics of naturally-occurring fragmented medial coronoid processes (FMCP) in order to help delineate potential pathophysiological events associated with FMCP.34 surgically excised FMCP from 21 client-owned dogs and 16 intact medial coronoid processes from 8 mongrel dogs were examined. The specimens were categorized by the dog's age: <12 months, 12–18 months, 18–24 months, >24 months.The excised FMCP and normal medial coronoid processes were sectioned and stained with haematoxylin and eosin, safranin-O fast green, and toluidine blue. Sections were subjectively evaluated for tissue morphology, cell and matrix content, and proteoglycan staining. Immunohistochemical staining was performed for collagen types II and X. Sections were then subjectively evaluated for the location and intensity of staining.FMCP tissue demonstrated a wide variety of histological and immunohistochemical characteristics compared to normal medial coronoid processes. Significantly (P = 0.016) more normal dogs stained positive for collagen type X than dogs with FMCP in the <12 months old group. No other significant differences between affected and normal dogs were noted for either collagen type in any age group. No significant difference in age was noted for the presence or absence of collagen type II among affected dogs, and no statistically significant correlation was observed between age of those with collagens type X and type II present. Although not statistically significant (P = 0.100), there was a trend for the presence of collagen type II when collagen type X was present. The results of this study have not provided a definitive answer regarding the role of collagen type X in the etiopathogenesis of FMCP, but suggest that it may be an important factor in some cases, warranting further investigation. Excised fragmented medial coronoid processes were examined to determine the collagen immunohistochemical staining characteristics when compared to intact processes.
Keywords: Fragmented medial coronoid process; collagen type II; collagen type X; immunohistochemistry